PENGARUH VARIASI LAMA KONTAK TANAMAN AZOLLA MICROPHYLLA TERHADAP PENURUNAN KADAR FOSFAT DAN COD PADA LIMBAH LAUNDRY - Nikita Rizky; Budiyono Budiyono; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2017)
Laundry is one kind of activities engaged in cloth laundering services. Laundry wastewater was discharged directly into the ditch and flowed to the river without treatment process. The level of COD and phosphate laundry wastewater was 761 mg/l, 20 mg/l exceeded the quality standard of Perda No. 5 of 2012. The research was aimed to know the effect of Azolla microphylla plants contact to the decrease of phosphate levels and COD. This kind of research used a quasi-experiment with the controlling group. The research object was the laundry liquid wastes from "Kurnia" laundry which produced waste approximately 25-30 liters per one washing.The analysis of data used one-way ANOVA test.The result of the research showed that the level of COD and phosphate in control were 585 mg/l; 10.24 mg/l, but the level of COD decreases in post experiment, i-e : the sixth day was  157 mg/l (14.67%),  the ninth day was 148 mg/l (16.85%), and the twelfth day was 90,4 mg/l (37.20%). While the phosphate concentration at the sixth day was 5.96 mg/l (19.05%), the ninth day was 5,69 mg/l (18.25%), and the twelfth day was 4.17 mg/l (19.34%). Level of COD showed the difference in average level decrease of COD laundry waste with variations in prolonged contact (p-value = 0.001). There was an decreased of COD laundry waste: between the variations in prolonged contact of six days and twelve  days (p-value = 0.002), the variation of 9 days and 12 days (p-value = 0.005). The most effective time of contact for decreasing to decrease the levels of COD was at the twelfth day, while results on phosphate laundry waste didn’t have the difference in average decrease levels of phosphate laundry waste with the variation of contact time (p-value = 0.52). Azolla microphylla plant could reduce the level of COD effectively at the 12 day, but it couldn’t reduce phospate level of  the laundry waste water